Light, natural ventilation system and growth regulators in micropropagation and volatile chemical analysis of Lippia gracilis Schauer (Verbenaceae) - Lazzarini, Luiz Eduardo Santos (2017)
Lippia gracilis Schauer (Verbenaceae), popularly known as ―alecrim de tabuleiro‖ is used in folk medicine to treat colds, coughs, sinusitis, bronchitis, headache and externally skin conditions, burns, wounds, and ulcers. The objective of this study was to establish the species in vitro and to evaluate the influence of light intensity and quality, natural ventilation systems and the use of growth regulators on the growth and on the chemical composition of the volatile fraction of L. gracilis . For in vitro establishment, the explant source (apical and nodal), origin (field and greenhouse), and culture medium (MS and MS/2) were evaluated. In the position experiment, the explants were horizontally and vertically inoculated. For the sucrose concentration experiments four concentrations were evaluated: 60, 30, 15 and 7.5 g L-1 of sucrose. Similarly, the salt concentration of culture medium experiment consisted of four salt concentrations (2MS, MS, ½ MS and ¼ MS). It is recommended to use nodal and apical segments from greenhouse for in vitro establishment of the species. The rate of multiplication and number of shoots was increased with the inoculation of explants in the horizontal position. It is recommended to use 30 g.L-1 of sucrose and ½ MS salt concentration. In the experimente of light intensity and quality, apical and nodal segments were cultivated for 30 days under the intensities of 26, 51, 69, 94 and 130 μmol m-2 s-1 obtained with cold white fluorescent lamps and under light emitting diodes (LEDs) blue; red; 1 blue: 2.5 red; 2.5 blue: 1 red, and white. For in vitro cultivation of L. gracilis , it is recommended to use red LEDs and high luminous intensities. In the natural ventilation systems experiment (SVN), nodal segments were cultivated with and without leaves for 35 days under a membraneless system (SM) and natural ventilation system with one (SVN1), two (SVN2), and four porous membranes (SVN4). It is recommended to use explants with one pair of leaves and four porous membranes. In the growth regulator experiment, 5 concentrations of BAP: 0.0; 0.5; 0.75; 1.00 and 1.25 mg L-1, and 3 ANA concentrations: 0.0; 0.5 and 1.0 mg L-1, in a factorial design were tested, and a second experiment with: 0.0 BAP + 0.0 TDZ; 0.25 BAP + 0.25 TDZ; 0.3 BAP + 0.2 TDZ; 0.2 BAP + 0.3 TDZ; 0.1 BAP + 0.4 TDZ; 0.4 BAP + 0.1 TDZ mg L-1. The combination between regulators stimulated the highest number of shoots and also significantly reduced carvacrol levels.